Using videoed stories to convey Indigenous ‘Voices’ in Indigenous Studies - Grogan, Justine; Hollinsworth, David; Carter, Jennifer (The Australian Journal of Indigenous Education, 2019)
Abstract Australian higher education policy espouses the need to expose students to Indigenous knowledges, cultures and pedagogies by embedding appropriate content into the curriculum. One way to overcome the challenges of guest speakers, lack of capacity and a crowded curriculum is to use digital materials regularly during lectures and tutorials. Videos have been shown to create empathy and emotional connection between students and the storyteller. The Voices project consisted of 12 semi-structured conversations with local Indigenous people covering a range of topics, each of which was edited for particular topics and courses to avoid student resistance to difficult material and avoid homogenous representations of Indigenous peoples. The edited video clips were shown in class and evaluated. This research reports on formal anonymous student feedback on teaching, questionnaire responses from 115 students and 10 in-depth interviews. Findings include the authenticity, emotional connection and empathy the storytellers provide, and the need for cultural courage to reflect on one's own positionality and privilege. We argue that digital storytelling is an effective pedagogy that also engages the community and helps further the higher education agenda for culturally inclusive knowledges and perspectives.